Gastroprotective and healing effects of hericium erinaceus (Bull.: Fr.) pers. extracts on ethanol-induced ulcers in sprague dawley rats / Wong Jing Yang - Wong, Jing Yang (2013)
Hericium erinaceus (Bull. Fr.) Pers. is a well-known culinary-medicinal mushroom that is used in traditional Chinese and Japanese cooking and herbal medicine to treat various human diseases. The objectives of the present investigation was to evaluate the gastroprotection and healing effects by aqueous extracts of the basidiocarps H. erinaceus against ethanol-induced gastric ulcers in rats. In acute toxicity study, all animals did not show any abnormal behavioural expressions and toxicological signs. Seven groups of rats were pre-treated orally with distilled water as the normal group; distilled water as ulcer group; 20 mg/kg of omeprazole as positive group; 50, 100, 200, and 400 mg/kg of extract as the experimental groups. One hour later, distilled water was given orally to the rats in normal group while ethanol was given orally to the ulcer control, positive control, and the experimental groups. The rats were sacrificed after an hour. Ulcer area, gastric wall mucus, gastric mucus barrier test, and histology and immunohistochemistry of the gastric wall were assessed. Gastric homogenates were analysed for Lipid peroxidation (LPO), superoxide dismutase (SOD), and catalase (CAT) content. The ulcer group exhibited significantly (p < 0.05) severe mucosal injury when compared to rats treated with omeprazole or extracts which showed significant (p < 0.05) protection against gastric mucosal injury. The mushroom extracts promoted protection as there was significant (p < 0.05) reduction of gross ulcer area. Further, the histological analysis showed marked reduction of edema and leucocytes infiltration in the submucosal layer when compared to the ulcer group. Immunohistochemistry studies showed up-regulation of HSP70 protein and down-regulation of Bax protein in rats pre-treated with extract. Significant (p < 0.05) increase in the mucus of gastric content and high levels SOD and CAT, reduced amount of LPO was observed in rats treated with mushroom extracts indicating the protective and / or healing effects of the mushroom extracts. During the three days ulcer treatment test, H. erinaceus extract at a dose of 400mg/kg could significantly (p < 0.05) heal the ulcer that was induced by ethanol in the rats.